THE ZIKIR CONCEPT AS A MEDIUM OF QUALITY SOUL - Ahmad Zuhri; Husnel Anwar; Muhammad Marzuki (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
This paper aims to examine the concept of remembrance as a medium of soul calm to better understand what the true meaning of the word remembrance contained in  Ar-Ra'd Surah verse 28 of the interpretation of Al-misbah is associated with the current modern era marked by the rapid advancement of science and technology and also followed by the advance of human civilization. The advancement of civilization and technology should be able to bring happiness, peace and tranquility of the soul more to humans themselves, but the facts that occur on the contrary, the progress of civilization and the development of science and technology actually impact the multidimensional crisis especially the neglect of the spiritual dimension and the dichotomy between the dimensions of technological progress with the dimension of spirituality, as a result will give birth to an advanced generation in civilization and technology but the spirit and soul are empty of happiness and calmness. This research was conducted by library research, namely library research. The data of this study were obtained based on a review of books relating to the concept of remembrance as a medium of soul calm in the books of the scholar of interpretation especially the interpretation of al-misbah by Quraish Shihab as the main source, this study uses management techniques and so on collecting data and making data special conclusion.The results of the study of the concept of remembrance as a medium for soul calm in  ar-ra sura verse 28 in the interpretation of al-Misbah describes how and what media of dhikzr are used to foster a sense of calmness and happiness of the soul.Keywords: remembrance, soul, calm.